Editor's Note. - González Crespo, Dr. Rubén (International Journal of Interactive Multimedia and Artificial Intelligence, 2022)
The International Journal of Interactive Multimedia and Artificial Intelligence – IJIMAI – provides an interdisciplinary forum in which scientists and professionals can share their research results and report new advances in Artificial Intelligence (AI) tools or tools that use AI with interactive multimedia techniques. The present regular issue includes 13 articles. The first block of articles deals with problems related to images as diverse as the artificial generation of images or the optimization of their storage and transmission through compression techniques. The applications are very diverse, including the identification of forgeries, tumors or even misplaced face masks. Another block contains only one paper on speech recognition targeted on specific users suffering from dysarthria. Other block of two articles focuses on the education field problems of automation of teachers’ certification processes or prediction of students’ academic failure. Last block of articles covers services and products, commerce, marketing and user experience issues, as well as the ethical implications of AI.